Answer:
a.
![x'_2+2x_2+3 x_1=0](https://img.qammunity.org/2020/formulas/mathematics/college/2hi9iatysgxpbjj7gl2agypbhycvs6h9q1.png)
b.
![x'_2+2x_2+x_1=0](https://img.qammunity.org/2020/formulas/mathematics/college/9j69wxg67zzryn1nedehyz4w3k28thd4eg.png)
Explanation:
We are given differential equation of second order in each part
We have to change given differential equation into first order differential equation
a.y''+2y'+3y=0
Suppose
![x_1=y(t)](https://img.qammunity.org/2020/formulas/mathematics/college/a6akzxqs96nj9xtcx1ya0w17h5rxvspemf.png)
![x_2=y'(t)](https://img.qammunity.org/2020/formulas/mathematics/college/ny7qn8ps1rsnk9hfo0eqg405u17vchr1vi.png)
Differentiate w.r.t times then we get
![x'_1=y'(t)=x_2](https://img.qammunity.org/2020/formulas/mathematics/college/iqzcfl8zfmdkd7g0idootde5ft6a805z49.png)
![x'_2=y''(t)](https://img.qammunity.org/2020/formulas/mathematics/college/rfsh6p5ghjq2tw913gy1ggvsb1cyuflr4q.png)
Substitute the values in the given differential equation then we get
![x'_2+2x_2+3 x_1=0](https://img.qammunity.org/2020/formulas/mathematics/college/2hi9iatysgxpbjj7gl2agypbhycvs6h9q1.png)
b.y''+2y'+y=0
Suppose
![x_1=y(t)](https://img.qammunity.org/2020/formulas/mathematics/college/a6akzxqs96nj9xtcx1ya0w17h5rxvspemf.png)
![x_2=y'(t)](https://img.qammunity.org/2020/formulas/mathematics/college/ny7qn8ps1rsnk9hfo0eqg405u17vchr1vi.png)
Differentiate w.r.t time
Then we get
![x'_1=y'(t)=x_2](https://img.qammunity.org/2020/formulas/mathematics/college/iqzcfl8zfmdkd7g0idootde5ft6a805z49.png)
![x'_2=y''(t)](https://img.qammunity.org/2020/formulas/mathematics/college/rfsh6p5ghjq2tw913gy1ggvsb1cyuflr4q.png)
Substitute the values in given differential equation
![x'_2+2x_2+x_1=0](https://img.qammunity.org/2020/formulas/mathematics/college/9j69wxg67zzryn1nedehyz4w3k28thd4eg.png)